Entre o som e o silêncio: a literatura ameríndia e o romance Órfãos do Eldorado de Milton Hatoum - Andrade, Edson Dorneles de (2014)
The novel Orphans of Eldorado (2008 ), by Milton Hatoum, brings into his narrative a number of references to Amazonian texts of different indigenous and riverine populations of the region of Manaus , Amazonia . Highlighting the indigenous elements , seems to build a deep dialogue with the call Amerindian literature , thus expanding the possibilities for analysis and interpretation of the work . The narrative is inspired by the myth of Eldorado , a possibly indigenous source of a series of records made throughout history that show the tense relationship between the colonial and post- colonial explorers in the Amazonian indigenous peoples and their lands . In addition to this story , other indigenous texts are cited and appear in the novel , composing a rich and heterogeneous scenario . To take account of this literary phenomenon , we mobilize our work in the categories of literary heterogeneity , intertextuality and rhizome , looking to make a broad approach that seeks to bring to the discussion the relevance of Amerindian substrate of the work , and show the importance of indigenous literature for this novel . We also consider it important to use the methodology of tensive semiotics to highlight gradations , the gradiência , and relationships , realizing the game of presence and absence of these indigenous elements that appear in the figures of sound, noise and silence. We believe that this work can contribute not only to compose the critical fortune of this novel , but to emphasize the importance of indigenous elements and indigenous reality in Brazilian literature and society.